Empowering Local Food Industries through Decision Support System (DSS): A Strategic Model for Sustainable MSME Development in Rural Indonesia - Rahmadhani Dynasti, Viona; Andini, Paramita; Shaban Maligisa, Haji (CV. SPDFHarmony, 2025)
Background: Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in driving local economic resilience and community empowerment in developing countries. However, traditional agro-based industries often face structural challenges such as weak management systems, limited access to technology, and unstructured financial documentation. The Home Industry Pia Tape Syam in Jember, Indonesia, exemplifies these constraints, operating within a competitive environment that demands digital adaptation and sustainable growth strategies. Integrating a Decision Support System (DSS) offers a transformative opportunity to improve managerial decision-making and enhance enterprise performance. Aims: This study aims to analyze the business feasibility and development strategies of Pia Tape Syam using the DSS-UMKM version 2.0 model to support sustainable and data-driven decision-making for rural agro-industries. Methods: A mixed-method approach combining qualitative and quantitative analyses was employed. Primary data were collected through structured interviews and financial documentation, followed by DSS-based computation assessing both non-financial (legal, marketing, production, management, and environmental) and financial aspects, including NPV, IRR, BCR, and Payback Period. Results: Findings reveal that environmental and production aspects achieved high feasibility scores, while legal and marketing factors require significant improvement. Financially, the enterprise demonstrated strong viability with an NPV of IDR 246,807,083.26, IRR of 48.72%, and a BCR of 1.75. These results confirm that the DSS approach effectively enhances strategic evaluation and investment decision accuracy in small-scale food industries. Conclusion: The study concludes that integrating DSS into rural MSMEs can significantly strengthen operational efficiency, financial sustainability, and adaptive capacity in a dynamic market environment. Beyond its economic benefits, DSS implementation fosters data literacy and managerial accountability, bridging the gap between traditional entrepreneurship and digital transformation. Hence, the DSS framework serves as a scalable model for empowering local food industries and advancing inclusive rural development across emerging economies.